Piano sonata no. 5 in C minor, op. 10, no. 1, edited by Liszt - Beethoven, Ludwig van, 1770-1827:::Creator::: (2025)
Piano sonata no. 5 in C minor, op. 10, no. 1, edited by Liszt for Holle's collected editions.